Pengaruh Literasi Keuangan dan Electronic Word Of Mouth (EWOM) Terhadap Perilaku Pembelian Impulsif Pengguna Tiktok Shop : Studi pada Mahasiswa UIN Raden Fatah Palembang - Pasha, Arkan; Rizki, Mulyani; Juniawati, Mutmainah (Pusat Riset dan Inovasi Nasional, 2026)
Advances in digital technology have changed consumption patterns among the general public, including students. Easy internet access, creative promotional strategies, and the integration of social media with e-commerce have increased the trend of online Shopping. TikTok Shop, as a rapidly growing platform, has successfully combined entertainment and transactions, thereby encouraging spontaneous Shopping behavior without planning. This study aims to analyze the influence of financial literacy and electronic word of mouth (eWOM) on the impulsive purchasing behavior of students at UIN Raden Fatah Palembang who use TikTok Shop. The study employs a quantitative method with a questionnaire administered to 100 respondents and multiple regression analysis. The results indicate that financial literacy does not significantly influence impulsive purchasing, while eWOM does have a significant influence. Simultaneously, both variables significantly influence such behavior. These findings indicate that financial literacy has not been able to curb impulsive behavior, while eWOM actually reinforces the urge to make spontaneous purchases on TikTok Shop..